'Gun! Gun! Gun!': An exploration of law enforcement officers' decision-making and coping under stress during actual events. Issue 8 (3rd August 2017) - Harris, Kevin R.; Eccles, David W.; Freeman, Carlos; Ward, Paul
Abstract: Research on decision-making under stress has mainly involved laboratory-based studies with few contextual descriptions of decision-making under stress in the natural ecology. We examined how police officers prepared for, coped with and made decisions under threat-of-death stress during real events. A delayed retrospective report method was used to elicit skilled police officers' thoughts and feelings during attempts to resolve such events. Reports were analysed to identify experiences of stress and coping, and thought processes underpinning decision-making during the event. Officers experienced a wide range of events, coped with stress predominantly via problem-focused strategies, and adapted their decision-making under stress based on the available context. Future officer training should involve a greater variety of training scenarios than is involved in current training, and expose trainees to the possible variants of each situation to foster better situational representation and, thus, a more reliable and adaptive mental model for use in decision-making. Practitioner Summary: This study concerns decision-making and coping strategies used by skilled police officers during real threat-of-death situations. Officers' decision-making strategies differed according to the complexity of the situation and they coped with the stress of these situations via attempts to resolve the situations (e.g. by planning responses) and, to a lesser extent, via attempts to deal with their emotions.